ERF1 delays flowering through direct inhibition of FLOWERING LOCUS T expression in Arabidopsis. Issue 10 (2nd August 2021) - Chen, Yanli; Zhang, Liping; Zhang, Haiyan; Chen, Ligang; Yu, Diqiu
ABSTRACT: ETHYLENE RESPONSE FACTOR1 (ERF1) is a key component in ethylene signaling, playing crucial roles in both biotic and abiotic stress responses. Here, we demonstrate that ERF1 also has an important role during floral initiation in Arabidopsis thaliana . Knockdown or knockout of ERF1 accelerated floral initiation, whereas overexpression of ERF1 dramatically delayed floral transition. These contrasting phenotypes were correlated with opposite transcript levels of FLOWERING LOCUS T ( FT ). Chromatin immunoprecipitation (ChIP) assays revealed that ERF1 associates with genomic regions of the FT gene to repress its transcription. ft‐10/ERF1RNAi plants showed a similar flowering phenotype to the ft‐10 mutant, whereas the flowering of FTox/ERF1ox mimicked that of FTox plants, suggesting that ERF1 acts upstream of FT during floral initiation. Similarly, altered floral transition in ethylene‐related mutants was also correlated with FT expression. Further analysis suggested that ERF1 also participates in delay in flowering‐time control mediated by the ethylene precursor 1‐aminocyclopropane‐1‐carboxylic acid. Thus, ERF1 may act as a negative modulator of flowering‐time control by repressing FT transcription in Arabidopsis . Abstract : Flowering plants have evolved sophisticated gene regulatory networks to coordinately govern floral initiation under suitable environmental conditions. ETHYLENE RESPONSE FACTOR1 functions as a negative modulator in the transmission of ethylene‐mediated flowering signals by directly associating with the FLOWERING LOCUS T promoter and repressing FLOWERING LOCUS T expression.